Enhancing students’ holistic reading through locally-enriched learning materials - Husni Mubarok; Haryanto Haryanto; Harun Joko Prayitno; Anam Sutopo; Miftachul Huda (Institute of Advanced Engineering and Science, 2026)
Learning materials that are suitable for the learning environment and resonate with students’ experiences play a crucial role in helping them learn English. A major obstacle in learning English is the scarcity of learning resources that incorporate local content, resulting in low holistic reading skills. This study aims to examine the effectiveness of locally-enriched learning materials on students’ holistic reading and to explore their responses. This study uses a mixed-method approach with a sample of 136 seventh-grade students in Indonesia. Data were gathered using tests, observation, and questionnaires, and analyzed using t-tests and descriptive statistics. The findings indicate that locally-enriched learning materials effectively enhance students’ holistic reading. This improvement is achieved by incorporating oral and written language skills, integrating local culture and daily activities into text discourse, and improving reading comprehension through vocabulary mastery, identifying main ideas, accuracy in grammar, and scanning. Learning enhancement was reflected in stages in English language teaching (ELT), the use of locally-enriched learning materials, material variations, teaching approach, participation and reading skill. Future research should concentrate on predicting text content and skimming in holistic reading. This study recommends the stakeholders to make policies in promoting local content as supporting learning materials in ELT.